Metal Ceramic Alloy Structure and Surface Layer Modification during Electron-Ion-Plasma Irradiation of Its Surface; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Ovcharenko V. E. Vladimir Efimovich; Ivanov Yu. F.; Shilko E. V.; Mokhovikov A. A. Aleksey Aleksandrovich; Yu Baohai; Xiong Tianyng; Xu Yun Hua; Zhong Lisheng (2016, 2016)
Title screen